Birth preparedness and complication readiness among Pokot nomadic pastoralists’ pregnant women in East Pokot district, Midwest- Kenya (2018)
Birth Preparedness and Complication Readiness (BPCR) is a strategy to promote the timely use of skilled maternal and neonatal care, especially during childbirth, based on the theory that preparing for childbirth and being ready for complications reduces delays in seeking health care and averts serious complications that women face during child birth. However, information on BPCR among Pokot nomadic pastoralists have not been well documented in literatures. The purpose of this research was to determine factors affecting BPCR among Pokot nomadic pastoralists’ pregnant women living in East Pokot District of Kenya. A cross-sectional facility based study was conducted among 275 Pokot pregnant women, above 18 years of age who were on their second and third trimesters and attending various Antenatal Clinics (ANCs) in East Pokot district. This was response rate of 90.1%. A multi-stage sampling technique was used and data was collected from those who met the inclusion criteria between August-October, 2017, using a pretested researcher administered questionnaire. The data collected was analyzed using (SPSS) version 21. Chi-square was used to test the hypothesis. A p-value of <0.05 was considered significant. The results showed that practice of BPCR was low (28%) among the respondents. Being educated (OR=18, CI=3.83-85.16) and having high household income (OR=2.53, CI=1.37-4.66) increased practice of BPC R. Ethnic affiliation to Pokot (OR=4.85, CI=1.38-17.07), practicing African Traditional Religion (OR=2.48, CI=1.44-4.26), practicing pastoralism (OR=2, CI=1.17-3.42) were found to significantly reduce the level of BPCR. In conclusion, birth preparedness and complication readiness was low among Pokot nomadic pastoralist’s pregnant women. There is a need for more BPCR awareness programmes targeting pastoralists’ women and other vulnerable groups in the region.